The moderating effect of firm age on capital structure choices: evidence from emerging markets - Matemilola, Bolaji Tunde; Kijkasiwat, Ploypailin; Liew, Chee Yoong (Springer Nature, 2024)
This research analyses how a firm’s age moderates the link between emerging market firm characteristics such as their profitability, firm size, asset tangibility, and their financing decisions (i.e., the level of leverage undertaken by these firms). Our empirical analysis reveals more evidence that firm age, as a firm-specific factor, not only amplifies the negative influence of profitability on leverage but also reinforces the adverse relationship between firm size and leverage. In addition, we also found that firm age weakens the positive relationship between asset tangibility and leverage. This research contributes to the corporate finance, corporate governance and emerging market finance literature by analysing how firm age influences the effects of emerging market firm characteristics. Additionally, this study contributes to the growing literature on the determinants of the gearing of firms, particularly on the role of firm-specific factors in explaining the variation in firms’ leverage. © The Author(s) under exclusive licence to Associazione Amici di Economia e Politica Industriale 2024.